2016
DOI: 10.1002/jbm.b.33643
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nanofiller-loaded poly (methyl methacrylate) bone cement composites for orthopedic applications: a review

Abstract: There is a large body of literature on new generations of poly (methyl methacrylate) bone cements that address one or more of the material's shortcomings. Among these are cements in which one of the constituents is a nanofiller, such as nano-sized barium sulfate, multiwalled carbon nanotubes, natural nanoclay, mesoporous silica nanoparticles, or oleic acid-capped silver nanoparticles. This article is a review of the literature on the properties of these nanofiller-loaded bone cements (NFLBCs). Some key charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 92 publications
2
27
0
Order By: Relevance
“…On the one hand, they demonstrated that the addition of the nanoparticles did not alter the mechanical properties of the cement and provided antibacterial effects against S. aureus and S. epidermidis [93]. The best antibacterial results were achieved with the quaternary ammonium chitosan nanoparticles, which was in agreement with other authors probably due to its higher surface density when compared to chitosan, as explained in [94].…”
Section: Polymethyl Methacrylate-based Cementssupporting
confidence: 86%
“…On the one hand, they demonstrated that the addition of the nanoparticles did not alter the mechanical properties of the cement and provided antibacterial effects against S. aureus and S. epidermidis [93]. The best antibacterial results were achieved with the quaternary ammonium chitosan nanoparticles, which was in agreement with other authors probably due to its higher surface density when compared to chitosan, as explained in [94].…”
Section: Polymethyl Methacrylate-based Cementssupporting
confidence: 86%
“…Injectable bone cements are crucial to the outcome of fractured vertebral body augmentation procedures, such as vertebroplasty (VP) and balloon kyphoplasty (KP). 1,2 PVP was introduced in 1987, by Galibert and Deramond 3 for the treatment of painful vertebral hemangiomas. PVP is a therapeutic interventional radiological procedure for pain relief and strengthening of the bone, involving the injection of a bone cement dough into a cervical, thoracic, or lumbar vertebral body lesion.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that our method can provide enhanced contrast without loss of the enhanced material strength. Wei et al24 also showed that gentamicin-doped HNTs added to PMMA could provide sustained gentamicin release without loss of material properties 17. In fact, gains in tensile strength and adhesion were observed.…”
Section: Discussionmentioning
confidence: 98%